Cover Image, Volume 76, Issue 1. Issue 1 (29th April 2019) - Perez, Adam M.; Thorner, Jeremy
Abstract : ON THE BACK COVER: The back cover image is based on the Research Article Septin‐associated proteins Aim44 and Nis1 traffic between the bud neck and the nucleus in the yeast Saccharomyces cerevisiae by Adam M. Perez and Jeremy Thorner, DOI:10.1002/cm.21524 .